A survey on gait recognition in IoT applications - Yu, Wang-Yang; Wang, Shui-Hua; Zhang, Yu-Dong (EAI Endorsed Transactions on Internet of Things, 2022)
In IoT applications, identity recognition is a basic and critical requirement. In recent years, IoT technology has developed rapidly, and IoT devices such as wearable devices, environmental sensors, and WiFi devices have been popularized and developed. The unobtrusive, low-cost, continuous advanced identity recognition methods are needed in IoT applications. Gait recognition not only has high performance but also is not easy to be forged or hidden. It has excellent potential in IoT intelligent identity recognition. This review discusses the implementation of gait analysis, representative datasets, and algorithms. Finally, we also discussed the challenges of gait analysis in IoT applications.